2018
DOI: 10.1038/s41401-018-0017-7
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba extracts prevent aortic rupture in angiotensin II-infused hypercholesterolemic mice

Abstract: Abdominal aortic aneurysms (AAAs) are a chronic vascular disease characterized by pathological luminal dilation. Aortic rupture is the fatal consequence of AAAs. Ginkgo biloba extracts (GBEs), a natural herb extract widely used as food supplements, drugs, and cosmetics, has been reported to suppress development of calcium chloride-induced AAAs in mice. Calcium chloride-induced AAAs do not rupture, while angiotensin II (AngII)-induced AAAs in mice have high rate of aortic rupture, implicating potentially differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…An abdominal aortic aneurysm is a vascular disease characterized by a luminal pathological dilatation, and one of its fatal consequences is the aortic rupture. To evaluate the therapeutic effect of EGB761 on the aortic rupture, Huang et al [1] administered angiotensin II (Ang II) in mice for 28 days, causing abdominal aortic aneurysm, and then administered EGB761 (100 mg/kg/day) for 56 days. It was possible to conclude that EGB761 prevents an aortic rupture in hypercholesterolemic mice, which were infused with Ang II, but only in the initial stage, restricting the protective range of this treatment in the mentioned comorbidity.…”
Section: Wistar Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…An abdominal aortic aneurysm is a vascular disease characterized by a luminal pathological dilatation, and one of its fatal consequences is the aortic rupture. To evaluate the therapeutic effect of EGB761 on the aortic rupture, Huang et al [1] administered angiotensin II (Ang II) in mice for 28 days, causing abdominal aortic aneurysm, and then administered EGB761 (100 mg/kg/day) for 56 days. It was possible to conclude that EGB761 prevents an aortic rupture in hypercholesterolemic mice, which were infused with Ang II, but only in the initial stage, restricting the protective range of this treatment in the mentioned comorbidity.…”
Section: Wistar Ratsmentioning
confidence: 99%
“…Oxidative stress is caused by destructive and progressive modifications in one or more body tissues, leading to dysfunction of organs, premature aging, and sometimes disease and death. It is a natural and fundamental process of the body, but it also involves the acceleration of destructive modifications over time, not only at the cellular level but also at the molecular level [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…65,66 Contrarily, GbE administration resulted in a significant drop in a lipid profile marker, which was consistent with research by Abdel-Zaher, Farghaly, 67 and Huang, Zhang. 68 The metabolization of radical scavengers and chain terminators like vitamin C and E, antioxidants like GSH, and redox regulatory enzymes like CAT, SOD, and glutathione peroxidase are just a few examples of the body's multiple defense mechanisms against free radicals. 69 In rats supplemented with CCl 4 , which may result in cell, tissue, or organ damage, the results of the current study showed a significant increase in the markers of oxidative stress while the levels of antioxidants significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In several epidemiological studies, dietary flavonol and flavonoid intake was inversely associated with the risk of cardiovascular disease ( 5 ). Current pharmacological investigations have revealed that the flavonoids extracted from G. biloba has prominent cardioprotective activities such as dilating blood vessels ( 6 , 7 ), regulating blood lipids ( 8 ), lowering blood sugar ( 9 ), inhibiting cardiomyocyte apoptosis ( 10 , 11 ) and preventing myocardial ischemic injury ( 12 , 13 ) and vascular rupture ( 14 ).…”
Section: Introductionmentioning
confidence: 99%